TECTONIC EVOLUTION AT MUSI HIGH AND ITS INFLUENCE TO GUMAI FORMATION AS ACTIVE SOURCE ROCK AT SOPA FIELD, SOUTH SUMATERA BASIN - Hendrawan Patra, Dimas
Shale from Lahat and Talang Akar Formations were widely accepted by many geoscientists as general source rocks in Palembang sub-Basin. The oil from Sopa Field was considered as hydrocarbon accumulation that had been migrated from local and regional deeps around Sopa Field, where Lahat and Talang Akar Formations were deposited. Based on subsurface physiographic that was obtained from integration of interpretation of well and seismic data, the closest deep is more than 20 km, therefore it is difficult to explain hydrocarbon migration mechanism from kitchen to reservoir. Besides that, Sopa Field is located at paleohigh since Eocene to Middle Miocene, consequently Lahat and Talang Akar Formations were not well developed. With these facts, reservoir carbonates of Baturaja Formation were deposited directly on the top of pre-Tertiary basement. This thesis is directed to obtain information of other formation potential as a source rock that charge hydrocarbon in Sopa Field, which is Gumai Formation. Not only act as regional seal in South Sumatera Basin, Gumai Formation may also act as active source rock, therefore this hypothesis must be proven with analytical geologic in a simple model. The result of comprehensive geochemical analysis shows that oils at Sopa wells migrated from source rock that had been deposited at transition environment. Oil from Sopa is correlated with bitumen that was extracted from sediment sample of Gumai. The sample of Gumai Formation was deposited at lagoon environment. On the other hand, extracted bitumen of Baturaja Formation sample was analyzed as non-indigenous or has been migrated from other sources. Therefore, the bitumen for sample of Baturaja Formation was not valid for further analysis. Seismic data interpretation is transformed into a geology model that will give explanations of maturity and migration mechanism of shale in Gumai Formation. Tectonic evolution at South Sumatera Basin since Middle Miocene to recent time, had been forming a massive number of thrust faults that make some blocks becoming higher, while the other was buried deeper. Some part of Gumai Formation at fault’s footwall was reached maturation zone. These tectonic evolutions was also made carbonate reservoir became tilted, therefore it helped hydrocarbon to move from the lower part to the shallower part. Hence, Gumai Formation is also acting as active source rock at Sopa Field. Gumai Formation has been proved as active source rock at Sopa Field, and it may open the new vision of hydrocarbon exploration with the same play. The model that was resulted from this thesis, may be used as an analog to define a source rock that younger than its reservoir.